The 1992 world book year book : the annual supplement to the world book encyclopeadia - World Book, Inc. (Chicago : World Book, 1992)
An encyclopedia designed especially to meet the needs of elementary, junior high, and senior high school students.
Includes bibliographical references and index.
Keywords: Encyclopedias and dictionaries; Encyclopedias and dictionaries